Komunikasi Inovasi dalam Membangun Daya Tarik Agrowisata Lembah Bambu Kuning di Desa Abung Jayo - Rama Buci Wiltar; Hagi Julio Salas (LPPM Institut Pendidikan Nusantara Global, 2026)
The development of locally based agrotourism requires continuous innovation supported by strategic communication to ensure sustainable competitiveness. While previous studies have largely focused on tourism promotion strategies or community empowerment communication, limited research has specifically examined innovation communication in independently managed agrotourism through Rogers’ Diffusion of Innovation framework. This study aims to analyze how innovation communication is constructed and diffused by the management of Lembah Bambu Kuning Agrotourism in Abung Jayo Village by emphasizing innovation attributes, communication channels, time, and the social system. This research employed a descriptive qualitative approach using in-depth observation, semi-structured interviews, and documentation. Informants included the owner, the social media manager, and five repeat visitors selected through purposive sampling. The findings reveal that innovation communication is not merely promotional but functions as a diffusion mechanism that shapes visitors’ knowledge, persuasion, and adoption stages. Digital platforms such as Instagram and TikTok serve as interactive communication channels that strengthen perceived relative advantage and observability of innovations through visual storytelling and live streaming. TikTok Live, in particular, enhances trialability and reduces uncertainty by enabling real-time clarification and engagement. Repeated exposure through algorithm-driven features such as the For You Page (FYP) accelerates awareness formation and influences visit decisions. However, minor discrepancies between online representations and on-site experiences highlight the importance of managing expectation congruence in innovation communication. Theoretically, this study extends Rogers’ diffusion of innovation perspective into the context of community-based agrotourism by demonstrating how digital interactivity reshapes diffusion processes in rural tourism settings. Practically, the findings offer strategic insights for small-scale tourism managers on designing adaptive, transparent, and participatory innovation communication to strengthen visitor trust and long-term sustainability.